Inhibitors using Aloe Vera to Reduce Corrosion of Carbon Steel HSLA X70 in saline media 3.5 M NaCl - Quispe-Avilés, Janeth Marlene (International Journal of Membrane Science and Technology, 2023)
The damage caused by corrosion in saline media affects carbon steel structures, so the use of inhibitors is a great alternative, however, industrial inhibitors have a high environmental impact. In search of sustainable alternatives, the present investigation investigated the inhibitory effect of aloe vera to reduce the corrosion of HSLA X70 steel by means of potentiodynamic polarization techniques and agar-agar gel, complementing microstructure characterization studies, the results show that 10%/V allows an efficiency of 82% to be able to protect X70 steel with great efficiency.